2021
DOI: 10.3390/antiox10020269
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Propolis in the Treatment of Periodontal Disease: Updated Systematic Review with Meta-Analysis

Abstract: In recent times, the use of natural products has gained momentum, either as a treatment or as adjuvants for other drugs in the treatment of different conditions. Propolis is a natural substance produced by bees which has proven useful for treating periodontal disease. This systematic review and meta-analysis gather evidence of the effectiveness of propolis in this kind of condition. The MEDLINE, CENTRAL, PubMed, EMBASE and Web of Science databases were searched for scientific articles to identify the findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 51 publications
0
25
0
5
Order By: Relevance
“…Similarly, the biological effect of propolis probably resulted from a combination of its known antibacterial [ 64 , 65 ], anti-inflammatory, and antioxidant properties [ 66 ]. In addition, topical application of propolis as an adjuvant to SRP was more effective than SRP alone, with regard to both microbiological [ 67 ] and clinical parameters [ 45 ]. The clinical improvement in Aloe vera-supplemented SRP can be attributed to its antibacterial [ 68 ] and anti-inflammatory [ 69 ] effects on periodontal bacteria, which consequently accelerate collagen synthesis and promote wound healing [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the biological effect of propolis probably resulted from a combination of its known antibacterial [ 64 , 65 ], anti-inflammatory, and antioxidant properties [ 66 ]. In addition, topical application of propolis as an adjuvant to SRP was more effective than SRP alone, with regard to both microbiological [ 67 ] and clinical parameters [ 45 ]. The clinical improvement in Aloe vera-supplemented SRP can be attributed to its antibacterial [ 68 ] and anti-inflammatory [ 69 ] effects on periodontal bacteria, which consequently accelerate collagen synthesis and promote wound healing [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature search was performed using the PubMed, Cochrane Library, and Web of Science databases to summarize the currently available knowledge and answer the aforementioned clinical question by isolating randomized controlled trials (RCTs) investigating the effects of antioxidants with periodontal treatment in patients with diabetes prior to 6 April 2021. The search terms related to antioxidants were set according to the previous studies [ 43 , 44 , 45 , 46 , 47 , 48 ]. The search terms used in PubMed are listed below:…”
Section: Methodsmentioning
confidence: 99%
“…Propolis is a viscous substance produced by bees that exhibits antimicrobial, anti-inflammatory, and antioxidant properties [ 13 , 14 ]. Propolis is well-documented in the scientific literature and is known to be non-toxic [ 15 ]. Propolis comprises over 200 ingredients, including flavonoids, cinnamic acids, caffeic acids, and caffeic acid phenethyl ester [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Propolis comprises over 200 ingredients, including flavonoids, cinnamic acids, caffeic acids, and caffeic acid phenethyl ester [ 16 ]. A meta-analysis on the effectiveness of propolis treatment for periodontitis has shown that it reduced probing pocket depth as compared with placebo [ 15 ]. Propolis has been locally delivered in various forms, such as mouthwash, toothpaste, irrigation, and subgingival gel [ 15 ], and has been reported to reduce plaque formation and exhibit antimicrobial effects against some key periodontal pathogens [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation